Determinacy Through Intertemporal Capital Adjustment Costs - Berthold Herrendorf; Akos Valentinyi (Hungarian Academy of Sciences, Institute of Economics, 2002)
It is well known that if mild sectorspecific externalities are considered, then the steady state of the standard two-sector real business cycle model can become locally indeterminate and endogenous business cycles can arise. We show that this result is not robust to the introduction of standard intertemporal capital adjustment costs, which may accrue when total capital is adjusted or when each sectors capital is adjusted. We find for both forms of adjustment costs that the steady state is determinate for all empirically plausible parameter values. We also find that determinacy occurs for a much larger range of parameter values when adjusting each sectors capital is costly.
Keywords: E0; E3; 330; capital adjustment costs; determinacy; local indeterminacy; local stability; sector-specific externality